Hunhu/Ubuntu as a Social Media Marketing Strategy Ethic in Post-Covid19 Times (London Journal of Research In Humanities and Social Sciences, 2024)
Ethics in professional lives is not a new thing. Ethics have been around for ages and today every profession has its modes and codes of conduct that their professionals live by. In any organisation members are expected to adhere to certain norms and practices in order to achieve the intended set goals. For this reason, this article argues and advocates for hunhu/ubuntu as an ethical rule or standard that should motivate and influence social media marketing activities in post-covid19 times. Without hunhu/ubuntu (good and love) social media marketing will not achieve its objectives and goals. Since it is within the nature and character of hunhu/ubuntu to transform and form social into human/real media marketing. Thus, it is the researcher’s argument that hunhu/ubuntu is the better and more reliable assured lens through which social media marketing can be assessed, boosted and supported visa-a-vie the terrible damaging effects of the corona pandemic. The nature of hunhu/ubuntu is the determining factor since the most basic concept in hunhu/ubuntu philosophy is vital force. And the basic interpretation/understanding is that hunhu/ubuntu is the vital and social media marketing is the force or power. In hunhu/ubuntu, vital and force are inseparable and thus constitute one thing, vital force. Hunhu/Ubuntu is always with its social media marketing as its natural, traditional, inherent and normal foundation or supporting pillar that vitalizes media marketing. Hunhu/Ubuntu is thus the intrinsic and hidden enduring aspect/component that rejuvenates and sustains social media marketing. Without the vitalizing influence and motivation of hunhu/ubuntu, social media marketing cannot stand but collapses; it remains a mere empty and unfulfilled social desire. Hunhu/Ubuntu is rich in moral qualities such as: hardworking, truthfulness, collaboration, solidarity, goodness and connectivity and these can be a moral backbone to social media marketing. It is within the essence of hunhu/ubuntu to endure, heal, restore and forgive the most atrocious wounds and damages covid19 pandemic has inflicted on media marketing. Hunhu/Ubuntu (love and good) determines the being, knowledge and logic of all things, social media marketing included.
Keywords: Auraco Tamed; Lope; indigenous body; Caupolic; hermeneutics.; textual theory; reader reception; aesthetic of reception; psychoanalytic theory; Alphonse Daudet; literary interpretation; adolescent readers; comprehension strategies; ethical appraisal; contemporary literary discourse.; Scientism; Modernity; Ethics; Cognitive Computing; Artificial Intelligence; COVID19; hunhu/ubuntu; vital force; social media marketing strategy and moral tool